Peran Akad Syirkah dan Mudharabah sebagai Instrumen Pembiayaan Usaha Produktif pada Lembaga Keuangan Syariah di Indonesia - Permatasari, Olivia; Queentanisha, Kayla Jingga; Zakhiah, Siska Lailatus; Anisya, Nur; Halizah, Fitria Hanina Nur; Putri, Amanda Amelia; Kurniawan, Taufiq (STAI Al Musaddadiyah Garut, 2025)
This study aims to analyze the role of shirkah and mudarabah contracts as financing instruments in supporting the development of productive enterprises within the Islamic economic sector. Both contracts are Sharia-based financial instruments grounded in partnership and profit-sharing principles, enabling collaboration between capital owners and business managers without involving elements of riba. This research employs a qualitative descriptive approach using a literature review method based on various sources, including SINTA-indexed journals, Islamic economics books, and DSN-MUI fatwas related to musyarakah and mudarabah financing. The findings indicate that the shirkah contract plays a role in establishing fair partnerships between capital and labor, while the mudarabah contract functions as a productive investment mechanism between financial institutions and small-scale entrepreneurs. Both contracts have the potential to enhance production capacity, promote Sharia-based entrepreneurship, and strengthen the real sector through profit-sharing financing systems. However, field implementation still faces challenges, such as low Sharia financial literacy and business management risks. The novelty of this study lies in its comparative analysis of shirkah and mudarabah contracts in the context of productive business financing, an area that has often been examined separately. These findings are expected to serve as a reference for Islamic financial institutions in optimizing sustainable partnership-based financing. Keywords: Shirkah Contract, Mudarabah Contract, Productive Financing, Islamic Economics, Profit Sharing.